The effect of HA380 blood adsorption on patients with acute infective endocarditis undergoing cardiac surgery: a retrospective study - Jiefei, Xiao; Lu, Cao; Han, Shi; Yongxu, Shi; Shaoyan, Mo; Kai, Qin; Yonghua, Li; Yanling, Zhu; Yumei, Jiang; Jian, Rong (Frontiers in Cardiovascular Medicine, 2025)
IntroductionSepsis is a major cause of ICU admission and mortality in patients with infective endocarditis patients. This study aimed to explore the effect of intraoperative HA380 blood adsorption on surgical outcomes in infective endocarditis patients, given its ability to adsorb inflammatory factors.MethodsWe retrospectively analyzed the clinical data of patients who underwent surgical treatment for infective endocarditis at our hospital. After propensity score matching, eligible patients were matched in a 1:1 ratio between HA380 users and non-users. The primary endpoint was the incidence of postoperative sepsis, while secondary outcomes included ICU stay, postoperative hospital stay, and the need for CRRT, IABP, and ECMO therapies. Laboratory results were compared at 24, 48, and 72 h postoperatively.ResultsA total of 148 patients were included in the analysis. After 1:1 matching, 39 pairs were further analyzed. There was no significant difference in the incidence of postoperative sepsis (20.5% vs. 15.4%, p = 0.724). However, HA380 patients had a significantly shorter postoperative hospital stay (21.2 vs. 28.1 days, p = 0.014), with no differences observed in the use of CRRT, IABP, or ECMO. Laboratory results showed that HA380 patients had significantly lower fibrinogen levels and a higher albumin-to-fibrinogen ratio.DiscussionThis study did not demonstrate a reduced risk of postoperative sepsis with HA380 blood adsorption. Although the HA380 group had a shorter postoperative hospital stay, lower fibrinogen levels, and a higher albumin-to-fibrinogen ratio, the overall effectiveness of HA380 requires further investigation.